The Implementation of Good Pharmacy Practice Standards at Pharmacies in Ha Dong District, Hanoi in 2018 - Thi Thanh Binh, Le; Duc Hoa, Vu; Doan Duy Linh, Nguyen; Thi Phuong, Pham; Thanh Trung, Nguyen; Xuan Bach, Nguyen; Dang Tuan, Mac (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 2DO - 10.25073/2588-1132/vnumps.4220, 2020)
This study describes the current implementation of the Good Pharmacy Practice (GPP) standards by a number of selected pharmacies in Ha Dong, Hanoi in 2018. Staff members of the selected pharmacies were interviewed using the questions developed based on the GPP standards. The analysis of the interview results shows that by qualification, the interviewed pharmacists fell into three groups: intermediate diploma, associate’s diploma and bachelor’s degree, accounting for 43.23%, 54.23% and 2.54%, respectively. All the studied pharmacies fully fulfilled the GPP requirements in terms of equipment for and arrangement of their functional areas. 74.58% of the pharmacies had their own drug stores; 11.86% of them practiced computerized business management. A hundred percent of the executive pharmacists well fulfilled their job duties, which guaranteed the availability of 100% of drug transactions for electronic search. However, 90.68% of the investigated pharmacies let their pharmacists make changes to prescriptions. As a concluding remark, although the selected pharmacies in Ha Dong district met the general GPP standards, the maintenance of the standards implementation, consultant pharmacist qualification and computerized management still need further improvement. Keywords GPP, pharmacies, Ha Dong district. References [1] Ministry of Health, Circular 02/2018/TT-BYT dated January 22, 2018. The Circular stipulates the roadmap for implementing the principles and standards of Good practice of drug retailing establishments, 2018 [2] To Hoai Nam, Analysis of the operation of pharmacies recognized as a "Good pharmacy practice - GPP" standard in Hanoi urban districts between 2010 and 2012, Hanoi University of Pharmacy, 2013. [3] Dinh Thu Trang, Analysis of pharmacies’ operation meeting the "Good pharmacy practice" - GPP in Thu Dau Mot City, Binh Duong Province in 2014, First Specialized Thesis, Hanoi University of Pharmacy, 2015. [4] Nguyen Thi Kim Anh, Analysis of pharmacies activities in Hai Duong city, First Specialized Thesis, Hanoi University of Pharmacy, 2016. [5] Tran Van Cuc, Assessing the status of GPP-compliant pharmacies in Da Nang city, Specialized Pharmacist Thesis 2, Hanoi University of Pharmacy, 2014. [6] Bui Thanh Nguyet, Analyzing the implementation of the "Good pharmacy practice - GPP standard" of pharmacies in Ho Chi Minh City in 2014, First Specialized Thesis, Hanoi University of Pharmacy, 2014 . [7] Ministry of Health, Circular 07/2017/TT-BYT of the Ministry of Health on promulgating the list of over-the-counter medicines, dated May 3, 2017 of the Minister of Health, 2017. [8] Vu Tuan Cuong, Analysis of implementation of applying "Good pharmacy practice - GPP standard" at drug retail establishments in Quang Ninh province, Second Specialized Thesis, Hanoi University of Pharmacy, 2010. [9] Huynh Thuc Lam, Analysis of implementation of good pharmacy practice (GPP) in Hon Dat district, Kien Giang province, Pharmacist Thesis, Tay Do University, Pharmacy – Nursing Specialty, 2017.